What is related to the choice of coping strategies? - functional relationship between a sense of self-efficacy, self-regulation and strategies for coping with stress - Molińska, Weronika; Olechowska, Anna (Kultura-Społeczeństwo-Edukacja, 2022)
Self-efficacy can affect an individual’s thoughts and emotions. It can be related to self-regulation processes and coping strategies. The aim of the study was to try to answer the question of whether there are correlations between the mentioned variables. To test this, an online survey was designed on the Google Forms platform, which included sociodemographic questions and three questionnaires: General Self-Efficacy Scale, COPE Inventory, Self Regulation Formative Questionnaire. The survey was prepared in English. The survey included 470 participants from Poland and Spain. The study was conducted during increased stress, which is the exam session. The result of the statistical analysis confirmed the accepted hypothesis. Strategies used in coping with stress are related to the level of selfregulation and self-efficacy. The higher the sense of self-efficacy, the more frequent the selection of favorable coping strategies, as well as the higher the level of self-regulation, the more frequent the selection of adaptive strategies and the rarer the selection of adaptive coping strategies. The results obtained are discussed in relation to the literature on the topic and previous studies, and it is suggested that further studies be conducted in a different context, taking into account that the results of self-efficacy or self-regulation could be different during intensified stress, for instance before or after an exam.